PERAN ISTRI YANG BERWIRAUSAHA DALAM MEWUJUDKAN KELUARGA SAKINAH DI DESA KAMPUNG REMPAK KABUPATEN SIAK, RIAU - Muamar Khadafi; Muhammad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Islamic law on the formation of a harmonious family in the marriage of an entrepreneur wife. The author will explain how the marriage of an entrepreneur wife couple, how Islamic law views their marriage and the formation of a harmonious family. This research is a qualitative field research. The author in obtaining data uses three data collection techniques, namely interviews, observation and documentation. The author uses data analysis techniques in the form of objective interpretations. The results of this study indicate that the involvement of wives in entrepreneurship effectively contributes to improving the family economy and, in turn, strengthens household harmony. A wife who is intelligent, adaptive, proactive in the economy, and maintains a domestic role and good communication, has proven to be a strong foundation for a harmonious, loving, and compassionate family. In addition, this study also reviews the first two Islamic legal reviews regarding women working outside the home. The first view, which is stricter, limits the role of women to the domestic sector, considering working outside the home to be contrary to nature. While the second view, which is looser, allows women to work in fields that are in accordance with the nature of women, although they still consider staying at home to be more important. Overall, this analysis highlights the dynamics and evolution of understanding of women's roles in society. Despite traditional interpretations, modern social needs and realities have encouraged flexibility, while still considering religious values and limitations